2019
DOI: 10.1111/febs.15108
|View full text |Cite
|
Sign up to set email alerts
|

Engineering transketolase to accept both unnatural donor and acceptor substrates and produce α‐hydroxyketones

Abstract: A narrow substrate range is a major limitation in exploiting enzymes more widely as catalysts in synthetic organic chemistry. For enzymes using two substrates, the simultaneous optimisation of both substrate specificities is also required for the rapid expansion of accepted substrates. Transketolase (TK) catalyses the reversible transfer of a C 2 -ketol unit from a donor substrate to an aldehyde acceptor and suffers the limitation of narrow substrate scope for industrial applications. Herein, TK from Escherich… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 55 publications
(72 reference statements)
0
24
0
Order By: Relevance
“…Similar results were obtained when a histidine in the substrate binding pocket of TK was replaced by 3MH. By analysing the crystal structures of TK complexed with donor substrates, the previous studies showed H100 of E. coli and yeast TK forms hydrogen bonds with the C1-hydroxy groups of its donor substrates including D-xylulose-5-phosphate (X5P) and D-fructose-6-phosphate (F6P) [ 38–40 ], and so switching the substrate to pyruvate would remove this hydrogen bond due to the lack of the hydroxyl group. Thus, we conjectured that by adding a methyl group to H100, its hydrophobic interaction with pyruvate may be enhanced, thus allowing the substrate to be anchored.…”
Section: Applicationsmentioning
confidence: 99%
“…Similar results were obtained when a histidine in the substrate binding pocket of TK was replaced by 3MH. By analysing the crystal structures of TK complexed with donor substrates, the previous studies showed H100 of E. coli and yeast TK forms hydrogen bonds with the C1-hydroxy groups of its donor substrates including D-xylulose-5-phosphate (X5P) and D-fructose-6-phosphate (F6P) [ 38–40 ], and so switching the substrate to pyruvate would remove this hydrogen bond due to the lack of the hydroxyl group. Thus, we conjectured that by adding a methyl group to H100, its hydrophobic interaction with pyruvate may be enhanced, thus allowing the substrate to be anchored.…”
Section: Applicationsmentioning
confidence: 99%
“…For example, in order to engineer transketolase (TK) to accept an unnatural donor (pyruvate) and acceptor (aliphatic or aromatic aldehydes), Yu et alperformedstructural alignment between TK and pyruvate decarboxylase (PDC). Furthermore, amino acid residues of TK, those around the substrate of PDC, were selected for mutagenesis (Yu et al, 2020). Thus, non-active sites could be considered good candidates for improving enzymeperformance.…”
Section: Enzyme Engineering For Improved Performance With Non-active Sites As Targetsmentioning
confidence: 99%
“…This forms a new asymmetric α-hydroxyketone with an (S)-configuration, which is otherwise difficult to prepare chemically. 6,7 WT and engineered TKs from different microbial sources have been used in the synthesis of phosphorylated sugars, 8 non-phosphorylated aliphatic and aromatic acyloins, [9][10][11][12][13] and rare sugars such as L-glucoheptulose, 14,15 as well as in coupled cascade reactions. [15][16][17][18] For synthetic applications, biocatalysis using enzymes such as TK allows a sustainable, one-step stereoselective way for preparing chiral building blocks and fine chemicals.…”
Section: Introductionmentioning
confidence: 99%